Bedside Clinical Hand-held Ultrasound in an Internal Medicine Department: The "Bed Med-Us" Experience of Codogno and its Clinical Utility in the Management of Diagnosis and Therapy in 1007 Patients - Giangregorio, Francesco; Mosconi, Emilio; Debellis, Maria Grazia; Palermo, Eliana; Provini, Stella; Mendozza, Manuela; Ricevuti, Laura; Esposito, Ciro (Ultrasound International Open, 2024)
Purpose Handheld ultrasound (HH-US) answers simple clinical questions in emergencies. We performed conventional US with HH-US at the patient’s bedside (BED) during a medical visit (MED) (BED MED-US). The purpose of this prospective study is to estimate BED MED-US reliability, its clinical impact in helping the clinician to formulate correct diagnoses, and its ability to save time and money.Materials and Methods 1007 patients (519 M; age:76.42) were assessed (from March 2021 to November 2022) in one or more districts. Final diagnosis was determined with clinical and reference tests (chest RX/CT, abdominal CT, endoscopy, etc.). Sensitivity, specificity, LR+ and LR-, and corresponding AUROC were evaluated. HH-US diagnoses were classified as: confirmation (HH-US revealed the sonographic signs that confirmed the clinical diagnosis) (CO), exclusion (HH-US excluded the presence of the ultrasound signs of other pathologies, in the clinical differential diagnosis) (EX), etiological (HH-US reaches diagnosis in clinically doubtful cases) (ET), or clinically relevant incidental (HH-US diagnoses that change the patient's process completely) (INC).Results HH-US reliability: true-pos: 752; true-neg: 242; false-pos: 7; false-neg: 6 (sens: 99.1%, spec: 97.6%, LR+: 98.5; LR-: 00.15, AUROC: 0.997); clinical impact: CO-diagnosis: 21%; EX: 25%; ET: 47%; INC: 7%; saved time and money: approximately 35,572 minutes of work and 9324 euros.Conclusion BED MED-US is a reliable clinical imaging system, with an important clinical impact both in diagnosis (etiological in 47%, incidental in 7%) and in the management of personnel resources.
Keywords: internal medicine; BED MED-US; point-of-care ultrasound; multi-site ultrasound; handheld ultrasound